POWER DOMINATION IN BYRON HOWARD & RICH MOORE’S ZOOTOPIA MOVIE - Sitepu, Setiana Sri Wahyuni; Rubiani, Annisa (EUFONI: Journal of Language, Literary, and Cultural Studies, 2020)
This study is aimed to uncover power domination in a film entitled Zootopia, directed by Byron Howard & Rich Moore. The directors portray how power domination occurs in the protagonist character in the movie. Howard reveals that the shape or size of a person’s body does not hinder their dreams of becoming whatever they dream of. For example, if there are creatures that have large bodies, it does not mean they are the most powerful and feared by other creatures. Conversely, if there are small-bodied creatures, it does not mean they are always weak and are pessimistic people, who are afraid in any case, including realizing their dreams. Howard also believes that if we believe in our abilities, all the words of people who doubt our ability will not affect ourselves to stop and give up what we expect. In this case, the writer would analyze the power of domination based on their form of body shape and body size. In addition, the theory by Max Weber will be applied in this study. The result of this study disclose that physical appearance does not affect oneâ€™s power. It can be seen that even though the protagonist character has small body, she also has power domination. It is proven that she could compete fairly with her opponent who has a bigger body, has the right and high self-esteem in defending the truth, and can achieve her dreams even though her body is small. Keywords : Power domination, Zootopia, Max Weber, Children Literature.